883 Incidence of Leishmaniasis in a District General Hospital. (October 2012) - Damodaran, S; Erumbala, G; Abraham, D; Nirmal, S
Abstract : Aim: To study the incidence of Leishmaniasis in children under 5 years in a District General Hospital in the UK. Method: The microbiology records over 5-years (2005–2010) were reviewed. Inclusion criteria were age under 5 years and diagnosis of Leishmaniasis on bone marrow examination. Results: Two cases were identified. Case-1: A 15 month-old-girl, family from east Timur, referred from primary care with weight-loss and a non-healing skin ulcer. She appeared undernourished with pallor, pyrexia and hepatosplenomegaly. FBC showed pancytopenia. Bone marrow examination confirmed Leishmaniasis. Her mother had intrapartum Leishmaniasis. Case-2: A 22 month-old-boy presented with high fever and weight loss for 3 weeks. Examination confirmed pyrexia, pallor and hepatosplenomegaly. FBC revealed pancytopenia. Direct antigen test for Leishmania was positive. Leishmania Donovani complex was detected on bone marrow examination. There was no history of maternal infection. Both children were born in United Kingdom with no history of foreign travel. They both responded well to treatment with ambisome. Discussion: Leishmania Donovani, the protozoan parasite, is transmitted in endemic areas by the insect vector Phlebotomine sandfly. In non-endemic areas, transmission is vertical. The infection can lead to impairment in cell mediated immunity and a 100% mortality rate, if left untreated. Most cases of visceral Leishmaniasis occur in India, Bangladesh, Nepal, Brazil, and the Sudan. East Timor, although not endemic, has witnessed an upsurge of several confirmed cases recently. There was a history of maternal infection in only one of these two children. The source of infection in the other remains unidentified.